Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T15:42:45+01:00
A) {2x-5y=6 => 2x=6+5y => x=3+2,5y
3x-4y-2=0

3*(3+2,5y)-4y-2=0
9+7,5y-4y-2=0
9+3,5y-2=0
3,5y=-7 |:3,5
y=-2
x=3+2,5*(-2)
x=-2

b) {y+5x=7 y=7-5x
x+2y=5

x+2(7-5x)=5
x+14-10x=5
9=9x |:9
x=1
y=7-5*1
y=2
2010-03-08T15:51:32+01:00
2x-5y=6 // :2 y+5x=7
3x-4y-2=0 x+2y=5
x=3+2,5y x+2*(7-5x)=5
3x-4y=2 x+14-10x=5
3*(3+2,5y)-4y=2 -9x=5-14
9+7,5y-4y=2 -9x=-9
3,5y=-7 x=1
y=-2

x=3+2,5y y=7-5x
x=3+2,5*-2 y=7-5*1
x=3-5 y=7-5
x=-2 y=2
2010-03-08T17:11:06+01:00
A) {2x-5y=6
2x=6+5y
x=3+2,5y
3x-4y-2=0

3*(3+2,5y)-4y-2=0
9+7,5y-4y-2=0
9+3,5y-2=0
3,5y=-7 |:3,5
y=-2
x=3+2,5*(-2)


x=-2



b) {y+5x=7 y=7-5x
x+2y=5

x+2(7-5x)=5
x+14-10x=5
9=9x |:9
x=1
y=7-5*1
y=2

Pozdro ;)